A Pneumatic Fingerless Soft Gripper for Envelope Gripping - Shuman Xu; Hongmei Du; Shangsheng Zhang; Ruicheng Lei; Jian Wang; Yulian Li; Zengzhi Zhang (Actuators)
In grasping operations, when facing unstructured environments, the use of soft-body grippers can be a good solution to the problem of grasping objects that are inconvenient to grasp due to their fragility and irregularity. However, as the soft-body gripper is composed of soft-body material, there are problems such as insufficient gripping power. The envelope-gripping method using a fingerless structure of the soft gripper has high gripping capacity. In this paper, a new type of pneumatic, soft-body, fingerless gripper (SFLG) is proposed based on envelope-type grasping. With its rigid connectors, it forms a soft-body gripper. By changing the air pressure and structure of the internal air cavity of the fingerless gripper, the degree of deformation can be controlled to achieve grasping of the object by the soft-body gripper. Experiments show that the soft-body gripper can grasp objects of different shapes and sizes. The SFLG can grasp objects up to 6 times higher than itself, and the soft gripper of this size can grasp objects up to 13 times heavier than itself. A pneumatic, fingerless, soft gripper has been designed to grasp small and heavy or tall objects in contrast to other fingerless soft grippers.